Analysing the Problem of Finding New Cases of Grade 2 Disabled Leprosy - Mahendra, Muamar Afdhal; Hendrati, Lucia Yovita (GLOBAL HEALTH SCIENCE GROUP, 2024)
The proportion of new leprosy cases with grade 2 disability in Lamongan Regency tends to increase and exceeds the programme target of <5% in 2019-2021. The discovery of new leprosy cases with grade 2 disability will illustrate the delay in early detection, resulting in a decrease in the quality of life of leprosy sufferers. Objective: The purpose of this study is to analyse the problem of delayed case finding of grade 2 disability in Lamongan District. Method: This study was a descriptive observational study. There were 9 informants in this study, namely, 1 person in charge of the leprosy programme at the Health Office, and 8 people in charge of the programme at the Puskesmas level. The methods used in identifying health problems were document study, brainstorming, USG (Urgency, Seriousness, Growth) method, and fishbone diagram. Results: Knowledge has an important role in determining a person's attitude, knowledge shows the intelligence that allows a person to act appropriately, quickly and easily in making decisions. Patients' lack of knowledge about the early symptoms of leprosy leads to inappropriate actions, so there are still new cases of leprosy with grade 2 disability in Lamongan Regency. Not only the patient's knowledge, but good family knowledge is also expected and is able to make appropriate leprosy treatment efforts. Awareness will grow in the family to make treatment efforts if the family has good knowledge. Conclusions: The priority problem in finding new cases of leprosy with grade 2 disability in Lamongan Regency is the lack of knowledge of patients and their families, which results in inappropriate behaviour when experiencing the first symptoms of leprosy.